2013
DOI: 10.1007/s00464-012-2604-x
|View full text |Cite
|
Sign up to set email alerts
|

Dried human amniotic membrane as an antiadherent layer for intraperitoneal placing of polypropylene mesh in rats

Abstract: Dried irradiated HAM does not prevent adhesion formation in intraabdominal peritoneal onlay PP mesh repair in rats. Any use of this biomaterial in adhesion prophylaxis must be undertaken respecting graft cell viability as much as possible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 31 publications
1
8
0
Order By: Relevance
“…However, there are limited studies on the use of AM in reconstruction of abdominal wall, all of which were experimental animal studies with conflicting outcomes (6,(25)(26)(27). The majority of these studies showed that AM is an effective antiadhesive barrier in polypropylene mesh repair of abdominal wall hernia (6,25,26). polypropylene mesh alone for the correction of abdominal wall defect in rats.It was found that although AM application did not alter the formation of adhesions after the first week of operation, it accelerated the healing as shown by increased inflammation and angiogenesis activity.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…However, there are limited studies on the use of AM in reconstruction of abdominal wall, all of which were experimental animal studies with conflicting outcomes (6,(25)(26)(27). The majority of these studies showed that AM is an effective antiadhesive barrier in polypropylene mesh repair of abdominal wall hernia (6,25,26). polypropylene mesh alone for the correction of abdominal wall defect in rats.It was found that although AM application did not alter the formation of adhesions after the first week of operation, it accelerated the healing as shown by increased inflammation and angiogenesis activity.…”
Section: Discussionmentioning
confidence: 99%
“…Further clinical studies should be conducted in order to confirm the study findings and to prove the clinical effectiveness of AM as an antiadhesive barrier so that it can 6 Iran Red Crescent Med J. In Press(In Press):e62788.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations